2021
DOI: 10.3389/fphar.2021.628924
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extracts of Cordyceps sinensis: Chromatography-based Metabolite Profiling and Protective Efficacy Against Hypobaric Hypoxia

Abstract: The toxicity and disposal concerns of organic solvents used in conventional extraction purposes has entailed the need for greener alternatives. Among such techniques, supercritical fluid extraction (SFE) has gained popularity by yielding extracts of high purity in a much faster manner. Carbon dioxide (CO2) is generally preferred as a supercritical solvent because of its lower temperature requirements, better diffusivity and easy removal. The present study describes the characterization of supercritical CO2 ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Other green alternatives to the use of organic solvents can be supercritical carbon dioxide extraction, a technique requiring low temperatures and treatment time, while providing good diffusivity ratio and extraction yields. A recent example can be the extracts from Cordyceps sinensis, containing flavonoids, nucleobases and volatile organic compounds, among other high‐quality components (Mishra et al ., 2021). Ultrasound‐assisted extraction has also revealed as an emerging system for the extraction of potentially mycoactive compounds.…”
Section: Extraction Technologies Of Mushroom Bioactive Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other green alternatives to the use of organic solvents can be supercritical carbon dioxide extraction, a technique requiring low temperatures and treatment time, while providing good diffusivity ratio and extraction yields. A recent example can be the extracts from Cordyceps sinensis, containing flavonoids, nucleobases and volatile organic compounds, among other high‐quality components (Mishra et al ., 2021). Ultrasound‐assisted extraction has also revealed as an emerging system for the extraction of potentially mycoactive compounds.…”
Section: Extraction Technologies Of Mushroom Bioactive Extractsmentioning
confidence: 99%
“…For this reason, these species could be considered as potential target viral inhibitors (Choengpanya et al ., 2021). The promising myotherapy treatment of hypobaric hypoxia condition by C. sinensis extracts was another example of the wide variety of possibilities that mushroom provides in the human medicinal field (Mishra et al ., 2021). Furthermore, it should be remembered that these resources could also be utilised for the treatment of different animal complications such as the antiparasitic control of gastrointestinal nematodes in order to prevent anthelmintic resistance.…”
Section: Bioactive Properties From Mushroomsmentioning
confidence: 99%
“…For example, polysaccharide extracts derived from medicinal mushrooms are commercially produced by a combination of ethanol and high-pressure water extraction which is time, labor, and energy-consuming [ 8 ]. In addition, some of these conventional techniques require toxic organic solvents, give low yields, can cause thermal degradation of active compounds, loss of volatile compounds, have low extraction selectivity, and can lead to the presence of residues in the desired compounds and final products [ 9 , 10 , 11 ]. All this has led to an interest in new extraction methods that will be ecologically and economically acceptable [ 12 , 13 ] and are merged under the term Green Extraction Technologies (GETs).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported increased recovery of phenolic compounds, carbohydrates, proteins, and minerals when compared with conventional extraction with shaking. Similarly, Mishra et al [ 10 ] optimized the supercritical CO 2 extraction parameters to obtain more bioactive Ophiocordyceps sinensis ( Cordyceps sinensis in the reference paper) extracts. This technique proved to be protective of mushrooms’ thermolabile compounds.…”
Section: Introductionmentioning
confidence: 99%